Possible genetic damage in the Czech nuclear power plant workers - Šrám, Radim J; Rössner, Pavel; Rubeš, Jiří; Beskid, Olena; Dušek, Zdik; Chvátalová, Irena; Schmuczerová, Jana; Milcová, Alena; Solanský, Ivo; Bavorová, Hana; Očadlíková, Danuše; Kopečná, Olga; et al. (Mutation research, 2006)
The aim of our study was to identify occupational risk of irradiation exposure in the Czech nuclear power plant workers. We analyzed levels of chromosomal aberrations, a well-known biomarker of early biological effects and a predictor of cancer risk. We applied the conventional method of cytogenetic analysis and fluorescence in situ hybridization (FISH, whole chromosome painting for chromosomes 1 and 4, combined with a pancentromeric probe) to three groups: 123 subjects in the Temelin nuclear power plant (2 years in use), 114 subjects in the Dukovany nuclear power plant (20 years in use), and 53 matched controls from Ceske Budejovice. Nuclear power plant workers were divided into two groups: subjects with admittance into the monitored zone, and others. Following factors were also analyzed: GSTM1, GSTT1, GSTP1, XPD, XRCC1, hOGG1, p53, MTHFR, and MS gene polymorphisms, levels of vitamins A, C, E, and folate in plasma, and level of cotinine in urine. Long-term exposure to ionizing radiation in the monitored zone was 0.47+/-1.50 mSv (miliSievert) in the Temelin nuclear power plant and 5.74+/-9.57 mSv in the Dukovany nuclear power plant. Using the conventional cytogenetic analysis, we observed 1.90+/-0.95 and 1.82+/-1.19% AB.C. (percent of aberrant cells) in the Temelin nuclear power plant, and 2.39+/-1.01 and 2.33+/-1.04% AB.C. in the Dukovany nuclear power plant, for monitored zone workers and others, respectively. In the control group, we found 2.25+/-0.82% AB.C. Genomic frequency of translocations F(G)/100 measured by FISH was 1.89+/-1.40 and 2.01+/-1.68 in the Temelin nuclear power plant, and 2.48+/-1.93 and 2.14+/-1.62 in the Dukovany nuclear power plant for monitored zone workers and others, respectively. In the control group, F(G)/100 was 1.83+/-1.19. Following factors were identified as potential confounders by the conventional cytogenetic analysis: XPD-6, by the FISH: age, GSTP1 and p53Bst genotypes, long-term use of medication, alcohol consumption, and smoking. No association between the dose of irradiation and the level of chromosomal aberrations in any nuclear power plant was detected either by the conventional cytogenetic analysis or by FISH.
Keywords: pracovní expozice; studie případů a kontrol; Humans; hybridizace in situ fluorescenční; Occupational Exposure; In Situ Hybridization, Fluorescence; Czech Republic; Cotinine; Financing, Organized; financování organizované; mužské pohlaví; Česká republika; Chromosome Aberrations; kotinin; lidé; Case-Control Studies; elektrárny; Power Plants; Male; chromozomální aberace